Zirconium carbide / silicon carbide ultra-high temperature ceramic composite material and preparation method thereof

The composite powder was prepared by surfactant coating and electrostatic adsorption self-assembly method, and the silicon carbide whiskers were treated by surface modification, which solved the agglomeration problem during the composite of zirconium carbide and silicon carbide, and improved the ultra-high temperature of zirconium carbide/silicon carbide The density, bending strength and oxidation resistance of ceramic composites.

CN118791318BActive Publication Date: 2024-12-13SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411288669.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

When zirconium carbide and silicon carbide are combined, it is difficult for the prior art to achieve uniform mixing, resulting in powder agglomeration, affecting density, bending strength, hardness and toughness.

Method used

By preparing cationic and anionic surfactant-coated zirconium carbide and nano-silicon carbide, the composite powder was prepared by electrostatic adsorption self-assembly method, and the silicon carbide whiskers were treated by aminolation and carboxylation to improve their dispersion and binding strength. Finally, it is sintered in an argon atmosphere.

Benefits of technology

The density, bending strength, toughness and oxidation resistance of zirconium carbide/silicon carbide ultra-high temperature ceramic composite materials are significantly improved, ensuring the stable performance of the material at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material and a preparation method thereof, belonging to the technical field of ultra-high temperature ceramic composite materials. The preparation method comprises the following steps: preparing composite powder, preparing composite silicon carbide whiskers, mixing, and sintering; the preparation of the composite powder comprises the following steps: preparing cationic zirconium carbide powder, preparing anionic nano-silicon carbide, preparing cationic nano-zirconium carbide, primary coating, and secondary coating; the preparation of the composite silicon carbide whiskers comprises the following steps: preparing amino silicon carbide whiskers, preparing carboxylated nano-zirconium carbide, and compounding; the preparation method of the invention can improve the thermal stability, toughness, oxidation resistance, density, flexural strength, and hardness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high temperature ceramic composite materials, and in particular to a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material and a preparation method thereof. Background Art

[0002] Ultra-high temperature ceramic composites are a type of composite materials with ceramic phases such as carbides or borides of transition metals as the matrix and particles and fibers as the toughening phase. They can maintain stable performance in ultra-high temperature environments and are the most promising ultra-high temperature thermal protection materials. They also have the advantages of high melting point, high hardness, high thermal conductivity, good thermal shock resistance, and moderate thermal expansion coefficient. They are mainly used in the production of aerospace heat-resistant protection devices, rockets, and fuel nozzles for various high-speed aircraft.

[0003] Zirconium carbide has a high melting point, high hardness, excellent bending strength, thermal stability, and chemical stability, but has a high densification sintering temperature, and poor toughness and oxidation resistance; Silicon carbide has excellent bending strength, oxidation resistance, corrosion resistance, wear resistance, and low friction coefficient, as well as excellent high-temperature mechanical properties, but poor toughness and thermal stability. The combination of zirconium carbide and silicon carbide can combine the advantages of zirconium carbide and silicon carbide to obtain high-performance ultra-high temperature ceramic composite materials.

[0004] When compounding zirconium carbide and silicon carbide, the most commonly used method is to use zirconium carbide as the base phase and silicon carbide as the reinforcement phase. Silicon carbide mainly exists in the zirconium carbide base phase in the form of particles or whiskers. When silicon carbide exists in the zirconium carbide base phase in the form of particles, the silicon carbide particles squeeze into the zirconium carbide grains under the action of pressure, occupy the position of filling pores, effectively inhibit the growth of zirconium carbide ceramic grains during sintering, play the role of fine grain strengthening, and thus improve the density of zirconium carbide; silicon carbide mainly improves the toughness of zirconium carbide through the toughening principle of microcracks and crack deflection; in addition, the addition of silicon carbide can also improve the oxidation resistance of zirconium carbide. When silicon carbide exists in the zirconium carbide matrix phase in the form of whiskers, the addition of whiskers can increase the barriers during sintering and inhibit the growth of zirconium carbide ceramic grains during sintering, thereby improving the density of zirconium carbide; silicon carbide mainly improves the toughness of zirconium carbide through the toughening principles of bridging and crack deflection; in addition, the addition of silicon carbide can also improve the oxidation resistance of zirconium carbide.

[0005] When compounding silicon carbide particles or silicon carbide whiskers with zirconium carbide, the most commonly used method is to directly mix silicon carbide particles or silicon carbide whiskers with zirconium carbide and then ball mill to obtain powder, and then sinter the powder after molding to obtain zirconium carbide / silicon carbide ultra-high temperature ceramic composite materials. However, it is difficult to evenly mix silicon carbide particles or silicon carbide whiskers with zirconium carbide by ball milling, and the obtained powder is easy to agglomerate, which affects the density of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite materials, and further affects the bending strength, hardness and toughness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite materials.

[0006] In order to solve the above problems, the most commonly used method at present is to mix a zirconium source, a silicon source, and a carbon source and then calcine them to obtain a zirconium carbide / silicon carbide composite powder, thereby avoiding the problem of powder agglomeration. However, after the base phase zirconium carbide and the reinforcing phase silicon carbide are composited, the toughening mechanism of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is mainly microcrack toughening. Specifically, after sintering, microcracks are generated between the base phase and the reinforcing phase during the temperature reduction process. The presence of microcracks can improve the toughness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, but the presence of microcracks will affect the flexural strength, hardness, and thermal stability of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material and a preparation method thereof, which can improve the thermal stability, toughness, oxidation resistance, density, flexural strength and hardness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, comprising the following steps: preparing a composite powder, preparing a composite silicon carbide whisker, mixing, and sintering;

[0010] The preparation of the composite powder comprises the following steps: preparing cationic zirconium carbide powder, preparing anionic nano-silicon carbide, preparing cationic nano-zirconium carbide, primary coating, and secondary coating;

[0011] The method for preparing the cationic zirconium carbide powder comprises mixing zirconium carbide powder, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol, stirring at room temperature at a stirring speed of 100-300 rpm for 20-30 minutes, adjusting the pH to 9-9.5, continuing stirring for 2.5-3 hours, centrifuging, taking the precipitate, washing it with deionized water for 3-4 times, and vacuum drying to obtain the cationic zirconium carbide powder;

[0012] In the preparation of the cationic zirconium carbide powder, the mass volume ratio of zirconium carbide powder, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol is 100-110 g: 30-35 g: 2500-2800 mL: 400-500 mL;

[0013] The average particle size of the zirconium carbide powder is 2 μm;

[0014] The anionic nano-silicon carbide is prepared by mixing nano-silicon carbide, sodium dodecyl sulfate, deionized water and anhydrous ethanol, stirring at room temperature at a stirring speed of 100-300 rpm for 20-30 minutes, adjusting the pH to 3-3.5, continuing to stir for 2.5-3 hours, centrifuging, taking the precipitate, washing it with deionized water for 3-4 times, and vacuum drying to obtain the anionic nano-silicon carbide;

[0015] In the preparation of anionic nano-silicon carbide, the mass volume ratio of nano-silicon carbide, sodium dodecyl sulfate, deionized water, and anhydrous ethanol is 100-110 g: 26-30 g: 2700-3000 mL: 450-500 mL;

[0016] The average particle size of the nano-silicon carbide is 100 nm;

[0017] In the preparation of cationic nano zirconium carbide, nano zirconium carbide, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol are mixed, stirred at room temperature at a stirring speed of 100-300 rpm for 20-30 minutes, the pH is adjusted to 9-9.5, stirring is continued for 2.5-3 hours, centrifuged, a precipitate is taken, washed with deionized water for 3-4 times, and vacuum dried to obtain cationic nano zirconium carbide;

[0018] In the preparation of cationic nano zirconium carbide, the mass volume ratio of nano zirconium carbide, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol is 100-110 g: 26-30 g: 2700-3000 mL: 450-500 mL;

[0019] The average particle size of the nano zirconium carbide is 100 nm;

[0020] The primary coating comprises mixing cationic zirconium carbide powder and deionized water, stirring at room temperature at a stirring speed of 100-300 rpm for 20-30 min, adding anionic nano-silicon carbide, continuing to stir for 5-6 h, centrifuging, taking a precipitate, washing it with deionized water 2-3 times, and vacuum drying to obtain a primary coating;

[0021] In the primary coating, the mass volume ratio of cationic zirconium carbide powder, deionized water, and anionic nano-silicon carbide is 100-105g:2800-3000mL:35-40g;

[0022] The addition rate of the anionic nano-silicon carbide is 4-5 g / min;

[0023] The secondary coating comprises mixing the primary coating material and deionized water, stirring at room temperature at a stirring speed of 100-300 rpm for 20-30 min, adding cationic nano zirconium carbide, continuing stirring for 5-6 h, centrifuging, taking the precipitate, washing it with deionized water for 2-3 times, and vacuum drying to obtain a composite powder;

[0024] In the secondary coating, the mass volume ratio of the primary coating, deionized water, and cationic nano zirconium carbide is 125-130 g: 3100-3500 mL: 45-50 g;

[0025] The addition rate of the cationic nano zirconium carbide is 4-5 g / min;

[0026] The preparation of composite silicon carbide whiskers comprises the following steps: preparing amino silicon carbide whiskers, preparing carboxylated nano zirconium carbide, and compounding;

[0027] The preparation of the amino-silicon carbide whisker comprises mixing β-type silicon carbide whisker, deionized water, anhydrous ethanol and 3-aminopropyltriethoxysilane, stirring and refluxing at 40-50° C. for 20-25 hours, centrifuging, taking the precipitate, washing it with deionized water for 3-4 times, and vacuum drying to obtain the amino-silicon carbide whisker;

[0028] In the preparation of the amino silicon carbide whisker, the mass volume ratio of the β-type silicon carbide whisker, deionized water, anhydrous ethanol, and 3-aminopropyltriethoxysilane is 50-52 g: 40-60 mL: 500-550 mL: 12-15 mL;

[0029] The average length of the β-type silicon carbide whiskers is 1 μm and the average diameter is 50 μm;

[0030] The method for preparing carboxylated nano zirconium carbide comprises mixing nano zirconium carbide, deionized water, anhydrous ethanol and 3-aminopropyltriethoxysilane, stirring and refluxing at 40-50° C. for 20-25 hours, centrifuging, taking a precipitate, washing the filter residue with deionized water for 3-4 times, vacuum drying, mixing with succinic anhydride and N,N-dimethylformamide, stirring and refluxing at room temperature for 15-16 hours, centrifuging, taking a precipitate, washing it with N,N-dimethylformamide for 3-4 times, and vacuum drying to obtain carboxylated nano zirconium carbide;

[0031] In the preparation of carboxylated nano zirconium carbide, the mass volume ratio of nano zirconium carbide, deionized water, anhydrous ethanol, 3-aminopropyltriethoxysilane, succinic anhydride, and N,N-dimethylformamide is 40-42 g: 40-60 mL: 500-520 mL: 12-15 mL: 10-11 g: 1700-2000 mL;

[0032] The average particle size of the nano zirconium carbide is 100 nm;

[0033] The composite comprises mixing carboxylated nano zirconium carbide, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and deionized water, stirring at 40-50° C. for 1-1.5 hours, adding amination silicon carbide whiskers, continuing stirring for 14-15 hours, centrifuging, taking a precipitate, washing it with deionized water for 3-4 times, and vacuum drying to obtain composite silicon carbide whiskers;

[0034] In the composite, the mass volume ratio of carboxylated nano zirconium carbide, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, deionized water, and amino silicon carbide whiskers is 220-250 g: 23-25 ​​g: 38-40 g: 2300-2500 mL: 280-300 g;

[0035] The mixing comprises mixing zirconium carbide powder, composite powder, composite silicon carbide whisker and anhydrous ethanol in a mass ratio of 70-80:35-40:9-12:750-850 and then ball milling to obtain slurry; drying and grinding the slurry to obtain powder;

[0036] The average particle size of the zirconium carbide powder is 3 μm;

[0037] The ball-to-material ratio during ball milling is 6-8:1, the rotation speed is 200-250rpm, and the time is 15-16h;

[0038] The sintering comprises adding the powder into a mold and sintering in an argon atmosphere to obtain a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material;

[0039] The sintering temperature is 1800-1850° C., the pressure is 30-35 MPa, and the sintering time is 60-70 min.

[0040] A zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared by the aforementioned preparation method.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The preparation method of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the toughness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material. The fracture toughness of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is 5.1-5.5 MPa·m 1 / 2 ;

[0043] (2) The preparation method of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the density of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, and the density of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is 98.4-98.8%;

[0044] (3) The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the flexural strength of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material. The flexural strength of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is 323-341 MPa;

[0045] (4) The preparation method of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the hardness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, and the Vickers hardness of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is 23.8-25.4 GPa;

[0046] (5) The preparation method of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the thermal stability of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, and the flexural strength of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material at 1600°C is 314-332MPa;

[0047] (6) The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material of the present invention can improve the oxidation resistance of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material. The mass change rate of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material after oxidation in an air atmosphere at 1300°C for 50 hours is 0.014-0.019%. DETAILED DESCRIPTION

[0048] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0049] Example 1

[0050] A method for preparing a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, specifically comprising:

[0051] 1. Preparation of composite powder:

[0052] (1) Preparation of cationic zirconium carbide powder: 100 g of zirconium carbide powder, 30 g of hexadecyltrimethylammonium bromide, 2500 mL of deionized water, and 400 mL of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 100 rpm for 20 min, the pH was adjusted to 9, stirring was continued for 2.5 h, centrifuged, the precipitate was taken, washed with deionized water three times, and vacuum dried to obtain cationic zirconium carbide powder;

[0053] The average particle size of the zirconium carbide powder is 2 μm;

[0054] (2) Preparation of anionic nano-silicon carbide: 100 g of nano-silicon carbide, 26 g of sodium dodecyl sulfate, 2700 mL of deionized water, and 450 mL of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 100 rpm for 20 min, the pH was adjusted to 3, and stirring was continued for 2.5 h. The precipitate was taken and washed with deionized water for 3-4 times, and then vacuum dried to obtain anionic nano-silicon carbide;

[0055] The average particle size of the nano-silicon carbide is 100 nm;

[0056] (3) Preparation of cationic nano zirconium carbide: 100 g of nano zirconium carbide, 26 g of hexadecyltrimethylammonium bromide, 2700 mL of deionized water, and 450 mL of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 100 rpm for 20 min, the pH was adjusted to 9, stirring was continued for 2.5 h, centrifuged, the precipitate was taken, washed with deionized water three times, and vacuum dried to obtain cationic nano zirconium carbide;

[0057] The average particle size of the nano zirconium carbide is 100 nm;

[0058] (4) Primary coating: 100 g of cationic zirconium carbide powder and 2800 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 100 rpm for 20 min, 35 g of anionic nano-silicon carbide was slowly added at a rate of 4 g / min, and stirring was continued for 5 h. The mixture was centrifuged, the precipitate was taken, washed twice with deionized water, and vacuum dried to obtain a primary coating;

[0059] (5) Secondary coating: 125 g of the primary coating material and 3100 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 100 rpm for 20 min, 45 g of cationic nano zirconium carbide was slowly added, and the addition rate was controlled to be 4 g / min. The stirring was continued for 5 h, centrifuged, and the precipitate was taken. After washing twice with deionized water, it was vacuum dried to obtain a composite powder;

[0060] 2. Preparation of composite silicon carbide whiskers:

[0061] (1) Preparation of amino-modified silicon carbide whiskers: 50 g of β-type silicon carbide whiskers, 40 mL of deionized water, 500 mL of anhydrous ethanol, and 12 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 40° C. for 20 h, centrifuged, and the precipitate was taken out. After washing with deionized water for 3 times, the precipitate was vacuum dried to obtain amino-modified silicon carbide whiskers;

[0062] The average length of the β-type silicon carbide whiskers is 1 μm and the average diameter is 50 μm;

[0063] (2) Preparation of carboxylated nano zirconium carbide: 40 g of nano zirconium carbide, 40 mL of deionized water, 500 mL of anhydrous ethanol, and 12 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 40 ° C for 20 h, centrifuged, and the precipitate was taken. The filter residue was washed with deionized water for 3 times, and vacuum dried. After that, it was mixed with 10 g of succinic anhydride and 1700 mL of N, N-dimethylformamide, stirred and refluxed at room temperature for 15 h, centrifuged, and the precipitate was taken. After washing with N, N-dimethylformamide for 3 times, it was vacuum dried to obtain carboxylated nano zirconium carbide;

[0064] The average particle size of the nano zirconium carbide is 100 nm;

[0065] (3) Composite: 220 g of carboxylated nano zirconium carbide, 23 g of N-hydroxysuccinimide, 38 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2300 mL of deionized water were mixed, stirred at 40 °C for 1 h, 280 g of amino-treated silicon carbide whiskers were added, and the mixture was stirred for 14 h. The mixture was centrifuged, and the precipitate was taken out. The mixture was washed with deionized water for 3 times, and then vacuum dried to obtain composite silicon carbide whiskers.

[0066] 3. Mixing: Mix zirconium carbide powder, composite powder, composite silicon carbide whisker and anhydrous ethanol in a mass ratio of 70:35:9:750 and then ball mill them, with the ball-to-material ratio during ball milling being controlled at 6:1, the rotation speed being 200 rpm, and the time being 15 hours to obtain slurry; dry and grind the slurry to obtain powder;

[0067] The average particle size of the zirconium carbide powder is 3 μm;

[0068] 4. Sintering: Add the powder into a mold and sinter in an argon atmosphere. The sintering temperature is controlled to be 1800°C, the pressure is 30 MPa, and the time is 60 minutes to obtain a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material.

[0069] This embodiment also provides a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared by the aforementioned preparation method.

[0070] Example 2

[0071] A method for preparing a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, specifically comprising:

[0072] 1. Preparation of composite powder:

[0073] (1) Preparation of cationic zirconium carbide powder: 105 g zirconium carbide powder, 32 g hexadecyltrimethylammonium bromide, 2600 mL deionized water, and 450 mL anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 200 rpm for 25 min, the pH was adjusted to 9, stirring was continued for 2.5 h, centrifuged, the precipitate was taken, washed with deionized water three times, and vacuum dried to obtain cationic zirconium carbide powder;

[0074] The average particle size of the zirconium carbide powder is 2 μm;

[0075] (2) Preparation of anionic nano-silicon carbide: 105 g of nano-silicon carbide, 28 g of sodium dodecyl sulfate, 2800 mL of deionized water, and 470 mL of anhydrous ethanol were mixed, stirred at 200 rpm for 25 min at room temperature, the pH was adjusted to 3, and stirring was continued for 2.5 h. The precipitate was taken and washed with deionized water for 3 times, and then vacuum dried to obtain anionic nano-silicon carbide;

[0076] The average particle size of the nano-silicon carbide is 100 nm;

[0077] (3) Preparation of cationic nano-zirconium carbide: 105 g of nano-zirconium carbide, 28 g of hexadecyltrimethylammonium bromide, 2800 mL of deionized water, and 480 mL of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 200 rpm for 25 min, the pH was adjusted to 9, stirring was continued for 2.5 h, centrifuged, the precipitate was taken, washed with deionized water three times, and vacuum dried to obtain cationic nano-zirconium carbide;

[0078] The average particle size of the nano zirconium carbide is 100 nm;

[0079] (4) Primary coating: 102 g of cationic zirconium carbide powder and 2900 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 25 min, 38 g of anionic nano-silicon carbide was slowly added at a rate of 5 g / min, and stirring was continued for 5.5 h. The mixture was centrifuged, the precipitate was taken, washed twice with deionized water, and vacuum dried to obtain a primary coating;

[0080] (5) Secondary coating: 128 g of the primary coating material and 3300 mL of deionized water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 25 min, 48 g of cationic nano zirconium carbide was slowly added at a rate of 5 g / min, and stirring was continued for 5.5 h. The mixture was centrifuged, the precipitate was taken, washed twice with deionized water, and vacuum dried to obtain a composite powder.

[0081] 2. Preparation of composite silicon carbide whiskers:

[0082] (1) Preparation of amino-modified silicon carbide whiskers: 51 g of β-type silicon carbide whiskers, 50 mL of deionized water, 520 mL of anhydrous ethanol, and 14 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 45° C. for 22 h, centrifuged, and the precipitate was taken out. After washing with deionized water for 3 times, the precipitate was vacuum dried to obtain amino-modified silicon carbide whiskers;

[0083] The average length of the β-type silicon carbide whiskers is 1 μm, and the average diameter is 50 μm;

[0084] (2) Preparation of carboxylated nano zirconium carbide: 41 g of nano zirconium carbide, 50 mL of deionized water, 520 mL of anhydrous ethanol, and 14 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 45 ° C for 22 h, centrifuged, and the precipitate was taken. The filter residue was washed with deionized water for 3 times, and vacuum dried. After that, it was mixed with 10.5 g of succinic anhydride and 1800 mL of N, N-dimethylformamide, stirred and refluxed at room temperature for 15.5 h, centrifuged, and the precipitate was taken. After washing with N, N-dimethylformamide for 3 times, it was vacuum dried to obtain carboxylated nano zirconium carbide;

[0085] The average particle size of the nano zirconium carbide is 100 nm;

[0086] (3) Composite: 230 g of carboxylated nano zirconium carbide, 24 g of N-hydroxysuccinimide, 39 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2400 mL of deionized water were mixed, stirred at 45 °C for 1 h, 290 g of amino-treated silicon carbide whiskers were added, and stirring was continued for 14.5 h. The mixture was centrifuged, and the precipitate was taken out. After washing with deionized water for 3 times, the precipitate was vacuum dried to obtain composite silicon carbide whiskers.

[0087] 3. Mixing: Mix zirconium carbide powder, composite powder, composite silicon carbide whisker and anhydrous ethanol in a mass ratio of 75:38:10:800 and then ball mill, control the ball-to-material ratio during ball milling to be 7:1, the rotation speed to be 220 rpm, and the time to be 15.5 h to obtain slurry; dry and grind the slurry to obtain powder;

[0088] The average particle size of the zirconium carbide powder is 3 μm;

[0089] 4. Sintering: Add the powder into a mold and sinter in an argon atmosphere. The sintering temperature is controlled to be 1820°C, the pressure is 32MPa, and the time is 65min to obtain a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material.

[0090] This embodiment also provides a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared by the aforementioned preparation method.

[0091] Example 3

[0092] A method for preparing a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, specifically comprising:

[0093] 1. Preparation of composite powder:

[0094] (1) Preparation of cationic zirconium carbide powder: 110 g of zirconium carbide powder, 35 g of hexadecyltrimethylammonium bromide, 2800 mL of deionized water, and 500 mL of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 300 rpm for 30 min, the pH was adjusted to 9.5, and stirring was continued for 3 h. The mixture was centrifuged, and the precipitate was taken. After washing with deionized water for 4 times, the precipitate was vacuum dried to obtain cationic zirconium carbide powder.

[0095] The average particle size of the zirconium carbide powder is 2 μm;

[0096] (2) Preparation of anionic nano-silicon carbide: 110 g of nano-silicon carbide, 30 g of sodium dodecyl sulfate, 3000 mL of deionized water, and 500 mL of anhydrous ethanol were mixed, stirred at 300 rpm for 30 min at room temperature, the pH was adjusted to 3.5, and stirring was continued for 3 h. The mixture was centrifuged, the precipitate was taken, washed with deionized water for 4 times, and vacuum dried to obtain anionic nano-silicon carbide;

[0097] The average particle size of the nano-silicon carbide is 100 nm;

[0098] (3) Preparation of cationic nano zirconium carbide: 110 g of nano zirconium carbide, 30 g of hexadecyltrimethylammonium bromide, 3000 mL of deionized water, and 500 mL of anhydrous ethanol were mixed, stirred at 300 rpm for 30 min at room temperature, the pH was adjusted to 9.5, and stirring was continued for 3 h. The mixture was centrifuged, the precipitate was taken, washed with deionized water for 4 times, and vacuum dried to obtain cationic nano zirconium carbide;

[0099] The average particle size of the nano zirconium carbide is 100 nm;

[0100] (4) Primary coating: 105 g of cationic zirconium carbide powder and 3000 mL of deionized water were mixed, stirred at 300 rpm for 30 min at room temperature, 40 g of anionic nano-silicon carbide was slowly added at a rate of 5 g / min, and stirring was continued for 6 h. The mixture was centrifuged, the precipitate was taken, washed three times with deionized water, and vacuum dried to obtain a primary coating.

[0101] (5) Secondary coating: 130 g of the primary coating material and 3500 mL of deionized water were mixed, stirred at 300 rpm for 30 min at room temperature, 50 g of cationic nano zirconium carbide was slowly added at a rate of 5 g / min, and stirring was continued for 6 h. The mixture was centrifuged, the precipitate was taken, washed three times with deionized water, and vacuum dried to obtain a composite powder.

[0102] 2. Preparation of composite silicon carbide whiskers:

[0103] (1) Preparation of amino-modified silicon carbide whiskers: 52 g of β-type silicon carbide whiskers, 60 mL of deionized water, 550 mL of anhydrous ethanol, and 15 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 50° C. for 25 h, centrifuged, and the precipitate was taken out. After washing with deionized water for 4 times, the precipitate was vacuum dried to obtain amino-modified silicon carbide whiskers;

[0104] The average length of the β-type silicon carbide whiskers is 1 μm and the average diameter is 50 μm;

[0105] (2) Preparation of carboxylated nano zirconium carbide: 42 g of nano zirconium carbide, 60 mL of deionized water, 550 mL of anhydrous ethanol, and 15 mL of 3-aminopropyltriethoxysilane were mixed, stirred and refluxed at 50 ° C for 25 h, centrifuged, and the precipitate was taken. The filter residue was washed with deionized water for 4 times, and vacuum dried. After that, it was mixed with 11 g of succinic anhydride and 2000 mL of N, N-dimethylformamide, stirred and refluxed at room temperature for 16 h, centrifuged, and the precipitate was taken. After washing with N, N-dimethylformamide for 4 times, it was vacuum dried to obtain carboxylated nano zirconium carbide;

[0106] The average particle size of the nano zirconium carbide is 100 nm;

[0107] (3) Composite: 250 g of carboxylated nano zirconium carbide, 25 g of N-hydroxysuccinimide, 40 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2500 mL of deionized water were mixed, stirred at 50 °C for 1.5 h, 300 g of amino-treated silicon carbide whiskers were added, and the mixture was stirred for 15 h. The mixture was centrifuged, the precipitate was taken, washed with deionized water for 4 times, and vacuum dried to obtain composite silicon carbide whiskers.

[0108] 3. Mixing: Mix zirconium carbide powder, composite powder, composite silicon carbide whisker and anhydrous ethanol in a mass ratio of 80:40:12:850 and then ball mill, control the ball-to-material ratio during ball milling to be 8:1, the rotation speed to be 250 rpm, and the time to be 16 hours to obtain slurry; dry and grind the slurry to obtain powder;

[0109] The average particle size of the zirconium carbide powder is 3 μm;

[0110] 4. Sintering: Add the powder into a mold and sinter in an argon atmosphere. The sintering temperature is controlled to be 1850°C, the pressure is 35 MPa, and the time is 70 minutes to obtain a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material.

[0111] This embodiment also provides a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared by the aforementioned preparation method.

[0112] Comparative Example 1

[0113] In this comparative example, based on the preparation method of Example 2, the first step of preparing the composite powder is omitted, and accordingly, the addition of the composite powder is omitted in the third mixing step; and silicon carbide powder with an average particle size of 3 μm is additionally added in the third mixing step, and the mass ratio of zirconium carbide powder, silicon carbide powder, composite silicon carbide whisker, and anhydrous ethanol is controlled to be 75:7.5:10:800.

[0114] Comparative Example 2

[0115] In this comparative example, based on the preparation method of Example 2, the step of preparing the composite silicon carbide whisker in step 2 is omitted, and accordingly, the addition of the composite silicon carbide whisker in the mixing step in step 3 is omitted; and in the mixing step in step 3, β-silicon carbide whiskers with an average length of 1 μm and an average diameter of 50 μm are additionally added, and the mass ratio of zirconium carbide powder, composite powder, β-silicon carbide whisker and anhydrous ethanol is controlled to be 75:38:5.6:800.

[0116] Performance Test 1

[0117] The toughness, density, flexural strength, Vickers hardness, and flexural strength at 1600° C. of the zirconium carbide / silicon carbide ultrahigh temperature ceramic composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The test results are shown in Table 1:

[0118] Table 1

[0119]

[0120] Performance Test 2

[0121] The mass change rate of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared in Examples 1-3 and Comparative Examples 1-2 after oxidation in an air atmosphere at 1300° C. for 50 hours was tested. The test results are shown in Table 2:

[0122] Table 2

[0123]

[0124] It can be seen from the performance test results that by adding composite powder and composite silicon carbide whiskers in the mixing step, the toughness, density, flexural strength, Vickers hardness, flexural strength at 1600°C, and oxidation resistance of the prepared zirconium carbide / silicon carbide ultra-high temperature ceramic composite material can be improved;

[0125] When preparing the composite powder, firstly prepare the cationic zirconium carbide powder, specifically, coat the surface of the zirconium carbide powder with the cationic surfactant hexadecyltrimethylammonium bromide; then prepare the anionic nano silicon carbide, specifically, coat the surface of the nano silicon carbide with the anionic surfactant sodium dodecylsulfonate; then prepare the cationic nano zirconium carbide, specifically, coat the surface of the nano zirconium carbide with the cationic surfactant hexadecyltrimethylammonium bromide; finally, self-assembly is performed, firstly, a layer of anionic nano silicon carbide is self-assembled on the surface of the cationic zirconium carbide powder by electrostatic adsorption, and then a layer of anionic nano silicon carbide is self-assembled by electrostatic adsorption. A layer of cationic nano zirconium carbide is added to obtain a composite powder; the cationic nano zirconium carbide on the surface of the composite powder can improve the fluidity of the composite powder and can also improve the mixing between silicon carbide and zirconium carbide. During sintering, the nano silicon carbide in the middle layer can enter and squeeze into the zirconium carbide grains to occupy the position of filling pores, and the nano zirconium carbide in the outermost layer can promote the growth and refinement of grains and can also form a transition layer to avoid the generation of micro cracks, thereby ensuring that the toughening mechanism of the obtained zirconium carbide / silicon carbide ultra-high temperature ceramic composite material is mainly particle toughening, and promotes densification and improves density;

[0126] When preparing composite silicon carbide whiskers, firstly, amino silicon carbide whiskers are prepared, specifically, 3-aminopropyltriethoxysilane is used to perform surface modification on beta silicon carbide whiskers to introduce amino groups; then, carboxylated nano zirconium carbide is prepared, specifically, 3-aminopropyltriethoxysilane is used to perform surface modification on nano zirconium carbide to introduce amino groups, and then succinic anhydride is used to react with amino groups to introduce carboxyl groups; finally, the amino silicon carbide whiskers and carboxylated nano zirconium carbide are mixed, and the amino groups react with the carboxyl groups to obtain beta silicon carbide whiskers coated with nano zirconium carbide, wherein the carboxyl groups on the surface of the nano zirconium carbide can promote the dispersion of the beta silicon carbide whiskers and avoid agglomeration, and the beta silicon carbide whiskers can further improve the toughness of the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material through the toughening principle of bridging and crack deflection; the presence of the nano zirconium carbide can also improve the bonding between the beta silicon carbide whiskers and zirconium carbide, reduce the interface effect, and improve the density.

[0127] At the same time, by respectively adopting electrostatic adsorption self-assembly and chemical grafting methods to prepare composite powders and composite silicon carbide whiskers, the problem of mutual influence between charges caused by adopting electrostatic adsorption self-assembly is avoided, and the dispersibility of composite powders and composite silicon carbide whiskers is further improved.

[0128] Unless otherwise specified, all percentages used in the present invention are by mass.

[0129] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material, characterized in that: The method comprises the following steps: preparing composite powder, preparing composite silicon carbide whiskers, mixing materials, and sintering; The preparation of the composite powder comprises the following steps: preparing cationic zirconium carbide powder, preparing anionic nano-silicon carbide, preparing cationic nano-zirconium carbide, primary coating, and secondary coating; The method for preparing the cationic zirconium carbide powder comprises mixing zirconium carbide powder, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol, stirring at room temperature, adjusting the pH to 9-9.5, continuing stirring, centrifuging, taking the precipitate, washing and vacuum drying to obtain the cationic zirconium carbide powder; The preparation of anionic nano-silicon carbide: nano-silicon carbide, sodium dodecyl sulfate, deionized water and anhydrous ethanol are mixed, stirred at room temperature, the pH is adjusted to 3-3.5, the stirring is continued, centrifuged, the precipitate is taken, washed and vacuum dried to obtain anionic nano-silicon carbide; The method for preparing cationic nano zirconium carbide comprises mixing nano zirconium carbide, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol, stirring at room temperature, adjusting the pH to 9-9.5, continuing stirring, centrifuging, taking the precipitate, washing and vacuum drying to obtain cationic nano zirconium carbide; The primary coating comprises mixing cationic zirconium carbide powder and deionized water, stirring at room temperature, adding anionic nano-silicon carbide, continuing stirring, centrifuging, taking the precipitate, washing, and vacuum drying to obtain a primary coating; The secondary coating comprises mixing the primary coating material and deionized water, stirring at room temperature, adding cationic nano zirconium carbide, continuing stirring, centrifuging, taking the precipitate, washing, and vacuum drying to obtain a composite powder; The preparation of composite silicon carbide whiskers comprises the following steps: preparing amino silicon carbide whiskers, preparing carboxylated nano zirconium carbide, and compounding; The preparation of the amino-modified silicon carbide whisker comprises: mixing β-type silicon carbide whisker, deionized water, anhydrous ethanol and 3-aminopropyltriethoxysilane, stirring and refluxing at 40-50° C., centrifuging, taking out the precipitate, washing and vacuum drying to obtain the amino-modified silicon carbide whisker; The preparation of carboxylated nano zirconium carbide comprises mixing nano zirconium carbide, deionized water, anhydrous ethanol and 3-aminopropyltriethoxysilane, stirring and refluxing at 40-50° C., centrifuging, taking a precipitate, washing, and vacuum drying, mixing with succinic anhydride and N,N-dimethylformamide, stirring and refluxing at room temperature, centrifuging, taking a precipitate, washing, and vacuum drying to obtain carboxylated nano zirconium carbide; The composite process comprises mixing carboxylated nano zirconium carbide, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and deionized water, stirring at 40-50° C., adding amination-modified silicon carbide whiskers, continuing stirring, centrifuging, taking precipitates, washing, and vacuum drying to obtain composite silicon carbide whiskers; The mixing method comprises mixing zirconium carbide powder, composite powder, composite silicon carbide whisker and anhydrous ethanol in a mass ratio of 70-80:35-40:9-12:750-850, and then ball milling to obtain slurry; and drying and grinding the slurry to obtain powder.

2. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the preparation of the cationic zirconium carbide powder, the mass volume ratio of zirconium carbide powder, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol is 100-110 g: 30-35 g: 2500-2800 mL: 400-500 mL; The average particle size of the zirconium carbide powder is 2 μm.

3. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the preparation of anionic nano-silicon carbide, the mass volume ratio of nano-silicon carbide, sodium dodecyl sulfate, deionized water, and anhydrous ethanol is 100-110 g: 26-30 g: 2700-3000 mL: 450-500 mL; The average particle size of the nano-silicon carbide is 100 nm; In the preparation of cationic nano zirconium carbide, the mass volume ratio of nano zirconium carbide, hexadecyltrimethylammonium bromide, deionized water and anhydrous ethanol is 100-110 g: 26-30 g: 2700-3000 mL: 450-500 mL; The average particle size of the nano zirconium carbide is 100 nm.

4. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the primary coating, the mass volume ratio of cationic zirconium carbide powder, deionized water, and anionic nano-silicon carbide is 100-105g:2800-3000mL:35-40g; The adding speed of the anionic nano-silicon carbide is 4-5 g / min.

5. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the secondary coating, the mass volume ratio of the primary coating, deionized water, and cationic nano zirconium carbide is 125-130 g: 3100-3500 mL: 45-50 g; The addition rate of the cationic nano zirconium carbide is 4-5 g / min.

6. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the preparation of the amino silicon carbide whisker, the mass volume ratio of the β-type silicon carbide whisker, deionized water, anhydrous ethanol, and 3-aminopropyltriethoxysilane is 50-52 g: 40-60 mL: 500-550 mL: 12-15 mL; The average length of the β-type silicon carbide whiskers is 1 μm and the average diameter is 50 μm; In the preparation of carboxylated nano zirconium carbide, the mass volume ratio of nano zirconium carbide, deionized water, anhydrous ethanol, 3-aminopropyltriethoxysilane, succinic anhydride, and N,N-dimethylformamide is 40-42 g: 40-60 mL: 500-520 mL: 12-15 mL: 10-11 g: 1700-2000 mL; The average particle size of the nano zirconium carbide is 100 nm.

7. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the composite, the mass volume ratio of carboxylated nano zirconium carbide, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, deionized water, and amino silicon carbide whiskers is 220-250g: 23-25g: 38-40g: 2300-2500mL: 280-300g.

8. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: In the mixture, the average particle size of the zirconium carbide powder is 3 μm; The ball-to-material ratio during the ball milling is 6-8:1, the rotation speed is 200-250rpm, and the time is 15-16h.

9. The method for preparing the zirconium carbide / silicon carbide ultra-high temperature ceramic composite material according to claim 1, characterized in that: The sintering: adding the powder into a mold and sintering in an argon atmosphere to obtain a zirconium carbide / silicon carbide ultra-high temperature ceramic composite material; The sintering temperature is 1800-1850° C., the pressure is 30-35 MPa, and the sintering time is 60-70 min.

10. A zirconium carbide / silicon carbide ultra-high temperature ceramic composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • High-strength silicon carbide ceramic material and preparation method thereof

    CN121021174A